Enveloped Viruses: Pathogenetic Targets for Cyanobacterial Lectins - N. N. BESEDNOVA; B. G. ANDRYUKOV; T. S. ZAPOROZHETS; S. P. ERMAKOVA; T. A. KUZNETSOVA; S. P. KRYZHANOVSKY; M. Y. SHCHELKANOV (Антибиотики и Химиотерапия)
Lectins are a group of highly specific carbohydrate-binding proteins with a wide spectrum of action, involved in the so-called «first line» of body defense. These unique biomolecules show high specificity for various mono- and oligosaccharides, primarily for viral and bacterial glycoconjugates. Cyanobacteria lectins are effective against enveloped viruses and are an appealing alternative to existing synthetic drugs. Virtually complete absence of resistance formation in viruses to these compounds is known. The purpose of this review is to analyze, summarize, and discuss the results of experimental studies in vivo and in vitro, illustrating the mechanisms of action and antiviral effects of lectins obtained from cyanobacteria in relation to the most dangerous and socially significant viruses: SARS-Cov-2, HIV, Ebola viruses, influenza, and hepatitis C. In addition, the article outlines some of the challenges that must be overcome in order to obtain effective antiviral drugs in the future.